Nutritive value of eight hybrid sorghum grains and three hybrid corns compared in all-concentrate rations, Part I: Hybrid sorghum and corn characteristics and methods used to nutritionally evaluate them - R.L. McCollough (Kansas Agricultural Experiment Station Research Reports, 1972)
In 1971, Kansas produced 234 million bushels of sorghum grain worth 217,000,000, second only to Texas. Most of it is used as an energy source in livestock rations. Since the introduction of hybrid sorghum grain in 1956, yield has increased 25%.
Keywords: Cattlemen& #x27; s Day; 1972; Report of progress (Kansas State University. Agricultural Experiment Station); 557; Beef; Hybrid sorghum grains; Hybrid corn